MANAJEMEN PELAYANAN PAJAK REKLAME TETAP OLEH DINAS PENDAPATAN DAERAH KOTA PONTIANAK DI SEPANJANG JALAN GAJAHMADA - Dini Febry Puspaningrum E.01109085 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The regulation problem of advertisement tax service authority remained in the city of Pontianak not support the implementation of regional autonomy, so that the Local Revenue Offices of Pontianak City perform a replanning in the management and collection of taxes to optimize the advertisement in the regional income. This study aims to determine the academic and understand the requirements to be met by the taxpayer in obtaining a Permanent Advertising Tax, advertising tax processing procedures remain to taxpayers, advertising tax services form fixed by the Local Revenue Offices of Pontianak City, the obstacles in the process of advertising tax processing remains, and experience in handling taxpayer fixed advertising tax. This study used qualitative methods. The design used phenomenological study of Littlejohn. To analyze more sharply, researcher used the theory of social construction of Peter L. Berger. From the results of research in the field, researcher found that the management of tax services performed by the Local Revenue Offices of Pontianak City especially on permanent advertising along Gajahmada Street, Benua Melayu Darat Village is not maximized. Researcher in the field of observation, advertising tax service management remains by the Local Revenue Offices of Pontianak City are hampered by the maintenance requirements are difficult to be met by the taxpayer, the maintenance procedure lasts long enough, the form of direct services have not been implemented to the fullest, as well as the barriers that interfere with the performance of the apparatus such as facility and inadequate infrastructure services. Recommendations in order to maximize service is taxpayer comply with the applicable regulations of the tax administration, the Local Revenue Offices of Pontianak City provide convenience to the taxpayer in process, and understand the differences of each taxpayer’s character. Keywords: Advertising Tax Service, Requirements, Procedures, Service Forms.